EFEKTIVITAS STRATEGI PROMOSI PARIWISATA EKOWISATA SITU GUNUNG SUKABUMI - Yulianti; Balilah, Euis; Sumarni, Sri; Herlina; Harijati, Roefaidah; Rahmat, Faris; Supiyandi, Dendi (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to empirically evaluate the influence of tourism promotion strategies on marketing effectiveness at the Situ Gunung ecotourism destination, Sukabumi Regency. In the context of sustainable tourism, promotion plays a crucial role in building awareness and a competitive destination image in the global market. Using a quantitative explanatory approach, this study involved 120 respondents selected through purposive sampling. Primary data were collected through structured questionnaires and analyzed using simple linear regression to examine the causal relationship between variables. The results indicate that promotion strategies have a positive and significant effect on destination marketing effectiveness. The regression coefficient of 0.73 shows that each improvement in promotion strategies significantly increases marketing effectiveness. Furthermore, the coefficient of determination of 0.61 indicates that promotion strategies account for 61% of marketing effectiveness, while the remaining variance is influenced by other factors beyond this study. The findings also reveal that social media is the most dominant information channel used by tourists (78%), particularly among the younger generation aged 18–30 years (62.5%). In conclusion, strengthening digital promotion strategies that integrate sustainability messages and authentic experiences is essential to enhance visit intention and tourist loyalty at Situ Gunung.